Construction of women's literary field in Nanyang Siang Pau’s women's supplement - Lee, Wei Min (2020)
Nanyang Siang Pau’s Women’s Supplement has played an extremely important role in constructing the literary field for women’s writing in late 80s’. The evolution of this change is tied closely to the supplement’s editor Qiao Ling. Her strong and vivid feminist consciousness has changed the style and image of the Women’s Supplement. As an editor of some literary magazines since the early days of her career, Qiao Ling has enriched herself with an abundant cultural capital, and gained wide network and good relations with many literary figures. She followed closely on local issues and applied localized perspectives in her work. She has provided a significant amount of space in the Women’s Supplement and invited local literary as well as non-literary writers to contrubite their ideas in women’s opinion and literary section. This research applies Feminist Theory and Pierre Bourdieu’s Field Theory of cultural production to explore the role of Nanyang Siang Pau’s Women’s Supplement in the construction of women’s literary field. It also examines the role of Qiao Ling in raising women’s consciousness through publishing special issues on relevant topics and establishing several columns for local writers, both men and women, to discuss on topics concerning women.